2023
DOI: 10.1001/jamanetworkopen.2023.39243
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Mindfulness Training for Interoception and Adherence to the DASH Diet

Eric B. Loucks,
Ian M. Kronish,
Frances B. Saadeh
et al.

Abstract: ImportanceHypertension is a major cause of cardiovascular disease, and although the Dietary Approaches to Stop Hypertension (DASH) diet lowers blood pressure (BP), adherence is typically low. Mindfulness training adapted to improving health behaviors that lower BP could improve DASH adherence, in part through improved interoceptive awareness relevant to dietary consumption.ObjectiveTo evaluate the effects of the Mindfulness-Based Blood Pressure Reduction (MB-BP) program on interoceptive awareness and DASH adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Mindful eating practices: Despite the limited literature on this topic, some evidence suggests that promoting mindful eating can help individuals become more aware of their eating habits and food choices. A randomized clinical trial involving 201 participants revealed that, at a 6-month follow-up, participants in the Mindfulness-Based Blood Pressure Reduction (MB-BP) program had a statistically significant improvement in their interoceptive awareness score by 0.54 points and their DASH score by 0.62 points compared to the control group [ 80 ]. These findings indicate that the 8-week MB-BP program can enhance adherence to DASH eating patterns, suggesting that mindful eating may lead individuals to pay more attention to their food selections and eating habits, thereby encouraging the choice of lower-sodium options.…”
Section: Modification Of Certain Eating Behavioursmentioning
confidence: 99%
“…Mindful eating practices: Despite the limited literature on this topic, some evidence suggests that promoting mindful eating can help individuals become more aware of their eating habits and food choices. A randomized clinical trial involving 201 participants revealed that, at a 6-month follow-up, participants in the Mindfulness-Based Blood Pressure Reduction (MB-BP) program had a statistically significant improvement in their interoceptive awareness score by 0.54 points and their DASH score by 0.62 points compared to the control group [ 80 ]. These findings indicate that the 8-week MB-BP program can enhance adherence to DASH eating patterns, suggesting that mindful eating may lead individuals to pay more attention to their food selections and eating habits, thereby encouraging the choice of lower-sodium options.…”
Section: Modification Of Certain Eating Behavioursmentioning
confidence: 99%